1994
DOI: 10.1021/jm00046a010
|View full text |Cite
|
Sign up to set email alerts
|

6,7,8,9-Tetrahydro-N,N-di-n-propyl-3H-benzindol-8-amines. Derivatives as Potent and Orally Active Serotonin 5-HT1A Receptor Agonists

Abstract: Derivatives and isosteric derivatives of the potent 5-HT1A agonist 8-(di-n-propylamino)-6,7,8,9- tetrahydro-3H-benz[e]indole-1-carbaldehyde (5) were prepared and evaluated in vivo and in vitro for serotonergic and dopaminergic activity. The 1-cyano analog 8 was found to be almost equipotent to 5 and the previously described 2-cyano derivative 6, while a 1-chloro and 1-(1,1,1-trifluoroethyl) substituent (9 and 10, respectively) formed less potent derivatives. The isosteric 6,7,8,9-tetrahydro-1H-benz[g]indoles 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Statistical comparisons: reserpine controls (striped columns) vs. NaCl (filled columns), and vs. corresponding TFMPPB-OH-DPAT (shadowed columns)-treated groups (t-test), tP < 0.01, and IrP c: 0.01, respectively. yielding EC50 and 95% confidence limits (CL), as described by Stjernlof et al (1994). The half-maximal 5-HT synthesis-reducing effect of TFMPP was obtained at 0.39 pM (CL 0.28-0.57).…”
Section: Reserpinementioning
confidence: 91%
“…Statistical comparisons: reserpine controls (striped columns) vs. NaCl (filled columns), and vs. corresponding TFMPPB-OH-DPAT (shadowed columns)-treated groups (t-test), tP < 0.01, and IrP c: 0.01, respectively. yielding EC50 and 95% confidence limits (CL), as described by Stjernlof et al (1994). The half-maximal 5-HT synthesis-reducing effect of TFMPP was obtained at 0.39 pM (CL 0.28-0.57).…”
Section: Reserpinementioning
confidence: 91%
“…For analytical purposes the mixed fraction was subjected to another chromatography (hexane/ ethyl acetate, 4:1-1:1), giving some pure fractions of the three possible isomers eluting in the named order. 17a: NMR (300 MHz, CDCls) d 0.95 (t, 3H), 1.20 (t, 3H), 1.65 (oct, 2H), 2.0 (m, 2H), 2.40 (q, 2H), 2.8-3.S (m, 6H), 4.0 (m, 0.25H), 4.45 (sept, 0.75H), 7.08 (dd (0.75) and dd (0.25), J = 8.4, 2.2 Hz, 1H), 7.47 (dd, J = 8.1, 2.2 Hz, 0.75H), 7.53 NMR (300 MHz, CDCls) d 0.95 (t, 3H), 1.20 (t, 3H), 1.60 (sxt, 2H), 2.0 (sxt, 2H), 2.35 (q, 2H), 2.S-3.3 (m, 6H), 4.03 (m, 0.25H), 4.45 (sept, 0.75H), 7.03 (quintet, 1H), 7.17 (m, 1H); MS m/e 308 (M+, 0.2), 116 (100), 176 (37), 57 (35), 223 (18). jV-(7-Amino-6-fluoro-l,2,3,4-tetrahydronaphthalen-2-yD-JV-propylpropionamide (18).…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6] In a series of articles, the tricyclic ring systems 8-(dialkylamino)-6,7,8,9-tetrahydrobenz[e]-and -[g]indoles were examined for their serotonergic activity. [7][8][9] This was initiated by the finding by Wikstrom et al8 that the unsubstituted 8-( dimethyl amino )-6,7,8,9-tetrahydrobenz[e]indole (3) displayed serotonergic activity at 5-HTia receptors, beside its previously reported dopaminergic activity.10 A subsequent paper from our group showed that the IV,IV-dipropyl analog of 3 (compound 4) is a potent 5-HTia agonist, although not selective with regard to dopamine D2 receptors. 9 In the same paper it was shown that introduction of a formyl group in the 1-position (compound 5 and enantiomers) altered the selectivity toward 5-HTia yielding one of the most potent 5-HTia agonists reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemistry. The biochemical experiments and the determinations of DOPA and 5-HTP by means of HPLC with electrochemical detection were performed as previously described.36•37 ED50 values were calculated by fitting a sigmoidal curve to the dose responses according to Stjernlof et al 38 The ED50 values are given in umol/kg. From these graphs, the doses of the drug yielding a half-maximal decrease (ED50 value) of the 5-HTP (the maximal effects, expressed as percent of controls, were as follows: limbic system, striatum, and the hemispheres = 50%) and the DOPA (the maximal effects, expressed as percent of controls, were as follows: limbic system = 35%, striatum = 20%, and the hemispheres = 50%) levels were estimated separately (Table 2).…”
Section: (R)-(+)-7-[[(trifluoromethyl)sulfonyl]oxy]-2-(«-propylamino)...mentioning
confidence: 99%